2018
DOI: 10.1088/1674-1056/27/2/027702
|View full text |Cite
|
Sign up to set email alerts
|

Multiple broadband magnetoelectric response in Terfenol-D/PZT structure

Abstract: In this paper, a novel magnetoelectric (ME) composite structure is proposed, and the ME response in the structure is measured at the bias magnetic field up to 2000 Oe (1 Oe = 79.5775 A•m −1 ) and the excitation frequency of alternating magnetic field ranging from 1 kHz to 200 kHz. The ME voltage of each PZT layer is detected. According to the measurement results, the phase differences are observed among three channels and the multi-peak phenomenon appears in each channel. Meanwhile, the results show that the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…Keeping the focus on PZT-based materials and changing the magnetostrictive phase to Terfenol-D, Wen et al [ 66 ] reported a ME coefficient of 10 V·cm − 1·Oe −1 suitable for broadband magnetic field sensors. A lead-free ME laminate composite consisting of thickness-polarized piezoelectric Mn-doped Na 0.5 Bi 0.5 TiO 3 -BaTiO 3 single crystal and length-magnetized magnetostrictive Tb 0.3 Dy 0.7 Fe 1.92 alloy (L-T mode) have been fabricated by Wang et al [ 67 ], exhibiting a linear ME response of 1.32 V·cm −1· Oe −1 that opened up the possibility for environment-friendly magnetic sensors.…”
Section: Ceramic-based Mementioning
confidence: 99%
See 1 more Smart Citation
“…Keeping the focus on PZT-based materials and changing the magnetostrictive phase to Terfenol-D, Wen et al [ 66 ] reported a ME coefficient of 10 V·cm − 1·Oe −1 suitable for broadband magnetic field sensors. A lead-free ME laminate composite consisting of thickness-polarized piezoelectric Mn-doped Na 0.5 Bi 0.5 TiO 3 -BaTiO 3 single crystal and length-magnetized magnetostrictive Tb 0.3 Dy 0.7 Fe 1.92 alloy (L-T mode) have been fabricated by Wang et al [ 67 ], exhibiting a linear ME response of 1.32 V·cm −1· Oe −1 that opened up the possibility for environment-friendly magnetic sensors.…”
Section: Ceramic-based Mementioning
confidence: 99%
“…Keeping the focus on PZT-based materials and changing the magnetostrictive phase to Terfenol-D, Wen et al [66] reported a ME coefficient of 10 V•cm − 1•Oe −1 suitable for broadband magnetic field sensors. A lead-free ME laminate composite consisting of thickness-polarized piezoelectric Mn- Upon magnetic field annealing an exceptionally high ME coefficient of 737 V•cm −1• Oe −1 at the mechanical resonance of 753 Hz and 3.1 V•cm −1• Oe −1 out of resonance at 100 Hz, at 6 Oe was demonstrated.…”
Section: Ceramic-based Mementioning
confidence: 99%
“…Because the elongation of the ferroelectric layer is not directly produced by the applied electric field but instead driven by the ferromagnetic layer, the interface coupling between the two phases becomes the key factor for an enhanced ME effect [34]. In order to reduce the influence of interface properties on the magnetoelectric response, many novel magnetoelectric structures are designed and prepared [34,35,36,37,38,39]. For example, Bi et al made the magnetic material into a groove and placed the piezoelectric layer in the groove.…”
Section: Introductionmentioning
confidence: 99%
“…Wen et al presented a novel ME structure, made up of one Terfenol-D layer and three PZT-5A layers, and showed that the three PZT-5A layers can be driven by one Terfenol-D layer simultaneously. The experimental results showed that multiple resonant frequencies and broad bandwidth characteristics existed in this ME structure [39].…”
Section: Introductionmentioning
confidence: 99%
“…Resonance is a dynamic problem, and large deformation also tends to occur; its analysis is beyond the scope of this investigation. Besides, the choice of component materials is also important to achieve strong coupling strength [16][17][18][19]. To fully explore this characteristic, ferromagnetic and ferroelectric materials with strong nonlinear hysteretic characteristics under an applied magnetic and electric field, respectively, are frequently investigated [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%